2012
DOI: 10.3174/ajnr.a3333
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted MRI: Distinction of Skull Base Chordoma from Chondrosarcoma

Abstract: BACKGROUND AND PURPOSE:Chordoma and chondrosarcoma of the skull base are rare tumors with overlapping presentations and anatomic imaging features but different prognoses. We hypothesized that these tumors might be distinguished by using diffusionweighted MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
90
6
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 16 publications
9
90
6
2
Order By: Relevance
“…The presence of the mucoid stroma results in relatively free extracellular water motion, which is in keeping with multiple studies in which elevated ADC values were found in other tumors that are composed of myxoid stroma, such as chordomas, chondrosarcomas, and myxoid soft-tissue tumors. 18,19 In addition, a component of cell vacuolization resulting in a decreased nucleus-to-cytoplasm ratio likely contributes further to an increase in the diffusivity of water in these tumors. Our findings differ from previously published data which reveal that atypical WHO grade II/III meningiomas show decreased ADC values consistent with a greater degree of restricted diffusion compared with that of typical WHO grade I meningioma subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the mucoid stroma results in relatively free extracellular water motion, which is in keeping with multiple studies in which elevated ADC values were found in other tumors that are composed of myxoid stroma, such as chordomas, chondrosarcomas, and myxoid soft-tissue tumors. 18,19 In addition, a component of cell vacuolization resulting in a decreased nucleus-to-cytoplasm ratio likely contributes further to an increase in the diffusivity of water in these tumors. Our findings differ from previously published data which reveal that atypical WHO grade II/III meningiomas show decreased ADC values consistent with a greater degree of restricted diffusion compared with that of typical WHO grade I meningioma subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…2 DWI could potentially be used to distinguish chordoma from chondrosarcoma because the ADC values for chordoma are lower than those for chondrosarcoma. 3,4 Moreover, the ADC values are lower in aggressive chordomas than in classic chordomas, suggesting that ADC may be useful for classifying chordomas into subcategories according to aggressiveness. 4 Hanna et al 5 suggested that a low T2 component in chordoma represented aggressive chordoma.…”
mentioning
confidence: 99%
“…3,4 Moreover, the ADC values are lower in aggressive chordomas than in classic chordomas, suggesting that ADC may be useful for classifying chordomas into subcategories according to aggressiveness. 4 Hanna et al 5 suggested that a low T2 component in chordoma represented aggressive chordoma. Classic and chondroid chordomas contain stromal mucin and chondroid matrix, respectively, which produce an increased T2 signal and a higher ADC, whereas an aggressive tumor contains less stroma with high cellularity and a lower ADC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…e read with great interest the recent article entitled "Diffusion-Weighted MRI: Distinction of Skull Base Chordoma from Chondrosarcoma" by Yeom et al 1 The authors showed, with a sample of 19 patients, that skull base chondrosarcomas could be differentiated from chordomas and from atypical chordomas by ADC values on diffusion-weighted MR imaging. This result represents a significant advance, because there are no other imaging approaches to reliably distinguish these central skull base tumors.…”
mentioning
confidence: 99%